Syair Tumitu wa Tuhyiyu Dalam Diwan al-Akhthal (Kajian Semiotika Riffaterre) - Saepul Millah (Fakultas Sastra Universitas Nahdlatul Wathan Mataram, 2020)
Literary work does not only mean a word but behind the words contain very deep meaning. This research tries to explore the deepest meaning of one of the poems by al-Akhtal in his Diwan Book entitled